The Sustainable Development Goals and Information and Communication Technologies - Peter Jones; Martin Wynn; David Hillier; Daphne Comfort (Indonesian Journal of Sustainability Accounting and Management, 2017)
The Sustainable Development Goals (SDGs) are a wide range of global sustainable development targets for the environment, society and economy and they were launched by the United Nations in 2015. In launching the SDGs, the United Nations called on all member states to embrace what are an ambitious and demanding set of challenges but it also emphasised the vital role that businesses, would have to play if these challenges were to be met. The aim of this preliminary commentary paper is to review a number of the ways the Information Communication and Technology industry believes it can contribute to the achievement of the SDGs. The paper outlines the characteristics of the concept of sustainable development and how ICT relates to sustainable development, reviews a number of the ways two leading ICT companies, namely Ericsson and Microsoft and two industry bodies, namely the GSMA which represents the interests of mobile operators worldwide, and the Global e-Sustainability Initiative, believe they can contribute to the achievement of the SDGs. The paper also examines some of the challenges the industry may face in making such a contribution and offers some reflections on the role of ICT in promoting the transition to a more sustainable future for people and the planet.